Techno-economic and life cycle assessment of membrane separation in post-combustion carbon capture: A review - Fu J.; Ahmad N.N.R.; Leo C.P.; Aberilla J.M.; Dela Cruz I.J.; Alamani B.; Koh S.P. (Elsevier B.V., 2025)
Carbon capture after combustion requires a proper system design with techno-economic evaluation and life cycle assessment to achieve the targeted efficiency with minimum energy consumption, cost, and environmental impacts. Learning past system design strategies and operating conditions through a systematic review of past studies is aimed at expanding novel membrane systems for post-combustion carbon capture in different industries and direct air capture. Past simulation studies revealed that membrane separation reduced energy consumption and carbon capture cost only if recycle streams, permeate at vacuum, and proper membrane selection were introduced into two-stage membrane systems. More than 90% of CO2 could be removed to produce CO2 with purity higher than 95%, using membrane systems with energy consumption as low as 1.0 MJ/kg CO2. Cryogenic, absorption, and other separation techniques could also be incorporated to form a hybrid carbon capture system with improved efficiency. However, the energy consumption of the hybrid systems should be well controlled. Studies on life cycle assessment showed that excessive energy consumption and synthetic polymeric membranes resulted in more environmental impacts, although the global warming effects were successfully reduced. Future membrane developments should focus on facilitated transport membranes derived from green materials, besides focusing on system design to bring down energy usage and operating costs in carbon capture. ? 2024 Elsevier B.V.